Valuation of Knowledge Management in Analysis of Blockades and Performances in Maturity Phases of the Startups - JAIN, DR MANJULA (The journal of contemporary issues in business and government, 2021)
The aim of this paper is to discusses and to find the alternative ways to tackle the barriers which one might be possibly face during the process of the business and during the running a group of the people as an organization or even to provide the services related to the queries come against any product while using by the people. The fact is that organizations must possess some high capabilities to meet expectations of the highly uncertain, cumbersome and motivated commercial market. The factors are needed to emphasis, to address the problem in the business and three factors are the agile organization, dynamic capabilities and knowledge management. A questionnaire session with the interview session have been used for the study and 85 people out of the 35 startup have been interviewed. These factors are spread among the field search, interviews, processes, approaches, in addition to the handling of the information. Innovation-stage start-ups with greater maturity, level of response growth and stage of innovation of scalability present an advanced degree use of knowledge management performs, approaches besides tools. It is predictable that the findings of research discussed in depth will be able to illustrate detailed examples of large-scale practices, procedures, and information reporting tools fashioned by organizations searching for start-ups to be operationally agile.